Evaluation Dutch preliminary nZEB requirements for hospital and university buildings - Maassen Wim (E3S Web of Conferences, 2019)
The need for (nearly) Zero Energy Buildings (nZEBs) in the Netherlands becomes increasingly important due to climate change, increasing energy prices, scarcity of fossil fuels and increasing geopolitical conflicts. In line with the EU EPBD, from 2020 new buildings, including hospital and university buildings, have to fulfil more strict energy requirements. Besides that, also the energy requirements for existing buildings will become stricter to realize an energy neutral built environment in 2050. On request of the Dutch Universities (WO) and the Dutch Academic Medical Centre’s (UMC), the Netherlands Enterprise Agency (RVO) assigned Royal HaskoningDHV to study the effect of the preliminary nZEB requirements on the real estate of the sector [1]. The feasibility of the nZEB requirements has been assessed for several representative, recently designed or realized buildings. For the selected hospital and university buildings, the results show that the preliminary nZEB requirements are not yet fulfilled. The requirement that 50% of building related energy should be of a local renewable energy source seems not to be feasible for both hospital and university buildings. Based on the results and recommendations of the study, a letter to the Dutch minister of the Ministry of the Interior and Kingdom Relations was sent and included a strong request to incorporate these in the definitive nZEB requirements, which will be set at the end of 2018.